1999
DOI: 10.1017/s0022029998003288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endocrine and paracrine factors on protein synthesis and cell proliferation in bovine hoof tissue culture

Abstract: Laminitis is a major cause of lameness in dairy cattle, and is widely attributed to a defect in the horny tissue that gives the hoof its mechanical strength. Defective horn is associated with, and may be preceded by, impaired keratin deposition in the hoof epidermis. The cause of abnormal keratin deposition is not easily identified but, like epidermal keratinization in other tissues, is likely to be controlled by hormones and the paracrine action of locally produced growth factors. The hormonal regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
0
19
1
4
Order By: Relevance
“…The helical arrangement of the intra tubular keratin, similar to the alfakeratin structure -main protein constituent of the keratinized epidermis -was also described by McKittrick et al (2012). The intercellular cement, second product of keratinization, adhering the keratinocytes and helping in the waterproofing of the hoof capsule and observed in the present study, was not reported in other research with buffaloes (Silva et al), yet it was described in equines (Hendry et al, 1999) (Fig. 4).…”
Section: Resultscontrasting
confidence: 52%
“…The helical arrangement of the intra tubular keratin, similar to the alfakeratin structure -main protein constituent of the keratinized epidermis -was also described by McKittrick et al (2012). The intercellular cement, second product of keratinization, adhering the keratinocytes and helping in the waterproofing of the hoof capsule and observed in the present study, was not reported in other research with buffaloes (Silva et al), yet it was described in equines (Hendry et al, 1999) (Fig. 4).…”
Section: Resultscontrasting
confidence: 52%
“…Maintenance of cows in this period on a high concentrate diet eventually creates hyperinsulinaemia and hyperglycaemia (VERMUNT and GREENOUGH, 1994), a condition in which insulin resistance develops, resulting in inhibition of glucose and amino acid uptake, and producing poor quality hoof horn. However, HENDRY et al (1999) identified the role of other factors, such as epidermal growth factor (EGF), relaxin, prolactin and cortisol levels at the time of late gestation that precipitate the production of poor quality keratin, thus leading to more likelihood of lameness during late lactation.…”
Section: Resultsmentioning
confidence: 99%
“…Production of another protein, keratin, is also important for conferring mechanical strength to the hoof wall and laminar interface. In bovine hoof explants cultured in vitro, cortisol significantly decreased keratin synthesis (Hendry et al 1999). Therefore, long-term effects of glucocorticoid use may conceivably produce a weakening of the lamellar bonds or inhibit growth from the coronary band.…”
Section: Catabolic Effectsmentioning
confidence: 99%